NILAI TUKAR PETANI KOMODITAS PERKEBUNAN - Chairul Muslim (Universitas Sebelas Maret, 2017)
Abstract : One indicator / measuring tool thatcan be used to assess farmers' welfareis Farmers Exchange Rate. This paper is part of the research result of PATANAS(Panel Petani Nasional) conducted by Indonesian Center for Agriculture SocioEconomic and Policy Analysis in Fiscal Year 2009-2012. More detail the purpose ofwriting this paper is to analyze Farmers Farmer's Exchange Rate (palm, cocoa,rubber and sugar cane) in Patanas villages. Primary data sources are farming effortsresulting from Patanas studies in 2008 and 2012 in four provinces, namely JambiProvince (representing rubber and palm oil), East Java (sugarcane), West Kalimantan(rubber and palm oil), and South Sulawesi (representing cocoa commodities).Secondary data obtained from local government related agencies. The result showsthat rubber NTP period of 2009-2012 shows positive that the price received is biggerthan the price paid, it shows that farmers are able to cover all cost components. NTPcocoa there is a decline in the exchange rate of income of 57.08%. This decline inexchange rates in line with the decline in the increase in the exchange rate of farmincome. Thus the exchange rate of cocoa farmers (NTP <100) means that thepurchasing power of farmers is relatively low, because the received is lower than theprice paid. NTP palms and sugar cane show a positive phenomenon (NTP> 100) offarm income can cover production costs so that the price received is greater than theprice paid, indicating better welfare of household life. Of course, the role of thegovernment to participate in increasing the income of farmers through the assistanceof subsidized agricultural input, provision of infrastructure; as well as policies forcontrolling household consumption expenditures (such as the provision of raskin subsidized education, health subsidies, etc.) are highly relevant in improving thewelfare of farmers. Abstrak : Salah satu indikator/alat ukur yang dapat digunakan untuk menilai tingkatkesejahteraan petani adalah Nilai Tukar Petani. Tulisan ini merupakan bagian hasilpenelitian PATANAS ( Panel Petani Nasional ) yang dilaksanakan oleh Pusat AnalisisSosial Ekonomi dan Kebijakan Pertanian pada Tahun Anggaran 2009–2012. Lebihdetail tujuan penulisan makalah ini adalah menganalisis Nilai Tukar Petani Kebun(sawit,kakao, karet dan tebu) di desa-desa Patanas. Sumber data primer adalah usahatani yang dihasilkan dari studi Patanas tahun 2008 dan 2012 di empat propinsi, yaituProvinsi Jambi, (mewakili komoditas karet dan sawit), Jawa Timur (tebu), KalimantanBarat (komoditas karet dan sawit), dan Sulawesi Selatan (mewakili komoditas kakao).Data sekunder didapat dari instansi terkait pemerintah daerah. Hasil menunjukkanbahwa NTP karet periode 2009-2012 menunjuukan positif artinya harga yangditerima lebih besar dari pada harga yang dibayarkan, hal ini menunjukkan bahwapetani mampu untuk menutupi seluruh komponen biaya. NTP kakao terjadi penurunannilai tukar pendapatan sebesar 57,08 persen Penurunan nilai tukar ini sejalan denganpenurunan peningkatan nilai tukar pendapatan usahatani. Dengan demikian nilai tukar petani kakao ( NTP<100) artinya kemampuan daya beli petani relative rendah, karenayang diterima lebih rendah disbanding harga yang dibayarkan. NTP sawit dan tebu menunjukkan gejala yang posif ( NTP>100) dari pendapatan usahatani dapat menutupibiaya produksi sehingga harga yang diterima lebih besar disbanding harga yangdibayar, menunjukkan kesejahteraan hidup rumahtangga yang lebih baik. Tentunyaperan pemerintah turut serta untuk peningkatan pendapatan petani melalui bantuansubidi saprodi, penyediaan infrastruktur; serta kebijakan untuk pengendalianpengeluaran konsumsi rumahtangga (seperti pemberian raskin, subsidi pendidikan,subsidi kesehatan, dan lainnya) dinilai sangat relevan dalam perbaikan kesejahteraanpetani.